2012
DOI: 10.1152/ajpheart.00660.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased preload on the force-frequency response and contractile kinetics in early stages of cardiac muscle hypertrophy

Abstract: Haizlip KM, Bupha-Intr T, Biesiadecki BJ, Janssen PM. Effects of increased preload on the force-frequency response and contractile kinetics in early stages of cardiac muscle hypertrophy. Am J Physiol Heart Circ Physiol 302: H2509 -H2517, 2012. First published March 30, 2012 doi:10.1152/ajpheart.00660.2011.-Numerous studies have aimed to elucidate markers for the onset of decompensatory hypertrophy and heart failure in vivo and in vitro. Alterations in the force-frequency relationship are commonly used as mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Trabeculae carneae and papillary muscles are often used in mechanical tests as a surrogate of the myocardium Fig. 1 Photograph of a human heart opened by a frontal incision illustrating the trabeculae carneae and papillary muscles 1 to understand its mechanical behavior [22,23]. For example, papillary muscles from rat and rabbit hearts have been used extensively in mechanical testing to understand the mechanical properties of the myocardium [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Trabeculae carneae and papillary muscles are often used in mechanical tests as a surrogate of the myocardium Fig. 1 Photograph of a human heart opened by a frontal incision illustrating the trabeculae carneae and papillary muscles 1 to understand its mechanical behavior [22,23]. For example, papillary muscles from rat and rabbit hearts have been used extensively in mechanical testing to understand the mechanical properties of the myocardium [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…These observations were made in a multicellular preparation, containing cardiomyocytes, fibroblasts, and endothelial cells. In this system, muscles have the ability to react to biochemical and mechanical stimuli and can remodel and adapt contractile function in a 24–48 hour time span [13] , [15] , [16] , [17] , [18] , [20] , [21] , [37] . Thus, results from this model may differ from other in vitro models in which isolated cardiomyocytes alone are investigated, or from whole-animal models where systemic regulation is present.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab and those of others have shown that these cultured multicellular preparations muscles remain stable in their protein expression/generation [15] and contractile function for up to 5 days [16] . Multicellular preparations can be used from various species [14] , [17] , including human [16] , and this system allows for functional protein product expression of virus-mediated gene transfer [18] , [19] and the observation of slow process such as load-induced changes in protein expression [13] , [20] or apoptosis [21] , [22] . Briefly, New Zealand White rabbits (1.5–2.0 kg) were heparinized and anesthetized by infusion of pentobarbital sodium (50 mg/kg) into the ear vein.…”
Section: Methodsmentioning
confidence: 99%
“…The load imposed on the cell in turn determines force of contraction and modulates phosphorylation and expression of myofilament proteins such as troponin I and desmin. Because of this relationship between tissue mechanical forces and the cardiac cell, chronic changes in elasticity and stiffness may subsequently lead to maladaptive growth [ 41 , 42 ].…”
Section: Ecm Mechanics At Different Scalesmentioning
confidence: 99%